Skin‐worn Soft Microfluidic Potentiometric Detection System. Issue 2 (22nd August 2018) - Sempionatto, Juliane R.; Martin, Aida; García‐Carmona, Laura; Barfidokht, Abbas; Kurniawan, Jonas F.; Moreto, Jose R.; Tang, Guangda; Shin, Andrew; Liu, Xiaofeng; Escarpa, Alberto; Wang, Joseph
Abstract: A flexible skin‐mounted microfluidic potentiometric device for simultaneous electrochemical monitoring of sodium and potassium in sweat is presented. The wearable device allows efficient natural sweat pumping to the potentiometric detection chamber, containing solid‐contact ion‐selective Na + and K + electrodes, during exercise activity. The fabricated microchip electrolyte‐sensing device displays good analytical performance and addresses sweat mixing and carry‐over issues of early epidermal potentiometric sensors. Such soft skin‐worn microchip platform integrates potentiometric measurement, microfluidic technologies with flexible electronics for real‐time wireless data transmission to mobile devices. The new fully integrated microfluidic electrolyte‐detection device paves the way for practical fitness and health monitoring applications. Abstract :